Teaching and learning about the relationships between land, violence and women's bodies: the possibilities of participatory visual methods as pedagogy. Issue 4 (2nd October 2018) - Flicker, Sarah; Sayde, Andrea; Hedlund, Kristina; Malivel, Garance; Wong, Kaila; Owino, Maureen; Booy, Sharon
Abstract: In 2016 the Women's Environmental Alliance and The Native Youth Sexual Health Network released their toolkit "Violence on the Land, Violence on our Bodies: An Indigenous Response to Violence." It maps the ways that settler colonialism and extractive industries create conditions of social and biological violence on Indigenous women's bodies in North America. As a white, cis-gender, female identified, settler professor, I assigned the toolkit to students enrolled in my Health and the Environment Masters class in the fall of 2018. Students were asked to create a cellphilm (short video made on a cellphone) to respond to the themes in the toolkit and write a short reflection. In this paper, we (my students and I) reflect on the toolkit, the assignment and what we learned about the relationships between land, violence and women's bodies. This paper summarises our teaching and learning journey together, with an emphasis on the possibilities of participatory visual methods as pedagogy for exploring these complicated issues.